Investigating the effect of exchange rate changes on transpacific rebalancing - Willem Thorbecke; Ginalyn Komoto (Asian Development Bank Institute (ADBI), 2010)
This paper investigates the role that exchange rate changes can play in rebalancing transpacific trade. It presents evidence from a gravity model indicating that the exports from the People's Republic of China (PRC) to the United States (US) are a key outlier in the global economy and that imbalances between the PRC and the US have remained large during the financial crisis that began in September 2008. It then reports that an appreciation of the yuan against the dollar would be required to rebalance bilateral trade between the US and the PRC. In the case of multilateral trade between the US and the rest of the world, on the other hand, the evidence indicates that a depreciation of the dollar would not substantially reduce the US global trade deficit. In the case of Asia's exports, results presented here and elsewhere indicate that: (i) sophisticated exports produced within regional production networks depend on exchange rates throughout the region; (ii) labor-intensive exports from developing Asian countries are strongly influenced by each country's own exchange rate; (iii) developing Asian countries compete extensively with each other in exports to third markets; (iv) a currency appreciation in developing Asia would increase capital and consumption goods imports; and (v) exchange rate volatility deters parts and components trade in Asia. These findings imply that Asia and the rest of the world would benefit if East Asian currencies could appreciate together against external currencies while maintaining relative currency stability within the region.
Keywords: F32; F41; 330; Zahlungsbilanzungleichgewicht; Wechselkursrisiko; Außenhandelseffekt; China; USA